2021
DOI: 10.1017/s2040174421000659
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet consumption programs male offspring to mitigate complications in liver regeneration

Abstract: In the last decades, obesity and nonalcoholic fatty liver disease (NAFLD) have become increasingly prevalent in wide world. Fatty liver can be detrimental to liver regeneration (LR) and offspring of obese dams (HFD-O) are susceptible to NAFLD development. Here we evaluated LR capacity in HFD-O after partial hepatectomy (PHx). HFD-O re-exposed or not to HFD in later life were evaluated for metabolic parameters, inflammation, proliferation, tissue repair markers and survival rate after PHx. Increasing adiposity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Although Nf2 gene expression dysregulation could be involved in NAFLD pathogenesis and progression to HCC ( Ardestani et al, 2018 ), the reduction in the transcript levels in the HF-O group 48h after PHx, compared to baseline, may be an indication that the pathway that controls cell repair is more permissive in this group after mechanical injury, similar to the CT-O. This result is supported by the findings of cyclin D1 content in the same model in our previous work ( Fante et al, 2021 ). Xiao et al (2005) suggested that the product of the Nf2 gene inhibits cell cycle progression through Cyclin D1 suppression since Nf2 gene silencing results in upregulation of cyclin D1 and S-phase entry.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Although Nf2 gene expression dysregulation could be involved in NAFLD pathogenesis and progression to HCC ( Ardestani et al, 2018 ), the reduction in the transcript levels in the HF-O group 48h after PHx, compared to baseline, may be an indication that the pathway that controls cell repair is more permissive in this group after mechanical injury, similar to the CT-O. This result is supported by the findings of cyclin D1 content in the same model in our previous work ( Fante et al, 2021 ). Xiao et al (2005) suggested that the product of the Nf2 gene inhibits cell cycle progression through Cyclin D1 suppression since Nf2 gene silencing results in upregulation of cyclin D1 and S-phase entry.…”
Section: Discussionsupporting
confidence: 73%
“… Xiao et al (2005) suggested that the product of the Nf2 gene inhibits cell cycle progression through Cyclin D1 suppression since Nf2 gene silencing results in upregulation of cyclin D1 and S-phase entry. We have shown that despite cyclin D1 showing a tendency to decrease in the HF-O group 48hs after PHx, the protein content still increases greatly in comparison to the baseline, being similar to the CT-O group and allowing the cell to enter the S-phase of the cycle, even with some delay ( Fante et al, 2021 ).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations